Language Acquisition On Early Deaf Children With Cochlear Implants In Inclusion Kindergarten - Yulvia Sani; Ossy Firstanti Wardany (Journal of ICSAR, 2022)
Deaf children  have problems in language acquisition due to hearing loss. Early use of cochlear implants can help  deaf children  listen and learn language and speech. This study aims to determine how language acquisition in early deaf students uses cochlear implants in an inclusive kindergarten in Bandar Lampung. This research is qualitative descriptive research. The methods of collecting data use interviews, observations, and documentation. The results showed that maximizing and familiarizing the hearing function can improve language acquisition. The use of cochlear implants accompanied by oral methods and rhythm sound awareness exercises assists in acquiring phonological, morphological, and semantic (linguistic awareness). Schools use the principle of learning by doing and integrating programs at home so that the process is more natural. In addition, it takes time for children to get accustomed to hearing and repeating what they hear. So it can conclude that using cochlear implants accompanied by the proper method can help the language acquisition of early  deaf children.